ANALISIS PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA INOVASI: STUDI PADA PERUSAHAAN MANUFAKTUR DI JAWA BARAT - Meirani Harsasi; Devi Ayuni (Universitas Trisakti, 2009)
Total Quality Management (TOM) is a topic that is often linked to company performance. Some studies showed that TOM has influence on performance, while some others showed contrary results. This study examined the effect of TQM on innovation performance of manufacturing companies in West Java. The method of data collection was conducted through mailed questionnaires, which consist of 155 respondents using purposive sampling. Multiple regression analysis is a statistical tool that was chosen to analyze the hypotheses. The results indicated that all TQM variables had significant influence on innovation performance. Keywords: TQM, innovation performance, Ma4ufacturing companies